Landslide risk reduction through close partnership between research, industry, and public entities in Norway: Pilots and case studies - Solheim, Anders; Kalsnes, Bjørn; Strout, James; Piciullo, Luca; Heyerdahl, Håkon; Eidsvig, Unni; Lohne, Jardar (Frontiers in Earth Science, 2022)
Cross-sectorial and cross-disciplinary collaboration, as well as public-private partnerships are necessary to handle the complexity of climate adaptation. The Research Council of Norway has established the Centres for Research-based Innovation (CRI) in which research- and education organizations, public entities and private enterprises join forces in 8-year long collaborations. CRI-Klima 2050 focuses on climate adaptation of buildings and infrastructure and runs several pilot projects to innovate new solutions for building resilience, stormwater- and landslide risk management. Several of the major infrastructure owners in Norway are partners in the centre. Norway is increasingly affected by precipitation triggered landslides. Klima 2050 pilot projects on landslide risk reduction include a web-based toolbox for prioritizing and choosing optimal mitigation measures, including Nature-Based Solutions, improved early warning systems and mitigation measures for slope instability, and improved local warning for hazardous weather systems, all developed in close collaboration between centre partners from different sectors and disciplines. The results of these projects can all be upscaled and are transferable to other infrastructure elements.